(untitled) (Journal of Pharmaceutical Negative Results, 2023)
This paper presents the fabrication and characterization of a composite material made with natural fibers namely Kenaf, Pine apple, and jute fibre in epoxy resin by hand layup method to study the mechanical properties of the proposed composite material as a base material for manufacturing of Dental implants. Hardness, impact, tensile strength, compressive strength tests have been conducted on these fabricated composites which were cut according to ASTM standards to study their mechanical properties. Test results exhibited significant improvement in mechanical properties for bilayer structure of the combination of Kenaf, Pine apple, and jute composite material when compared to other combinations of composite materials of this work. This work is very useful in making the composite material which is required for manufacturing of Dental implants.